2017
DOI: 10.3389/fnagi.2017.00213
|View full text |Cite|
|
Sign up to set email alerts
|

White Matter Changes-Related Gait and Executive Function Deficits: Associations with Age and Parkinson's Disease

Abstract: Background: White matter changes (WMC) are a common finding among older adults and patients with Parkinson's disease (PD), and have been associated with, e.g., gait deficits and executive dysfunction. How the factors age and PD influence WMC-related deficits is, to our best knowledge, not investigated to date. We hypothesized that advanced age and presence of PD leads to WMC-related symptoms while practicing tasks with a low complexity level, and low age and absence of PD leads to WMC-related symptoms while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
(107 reference statements)
2
4
0
1
Order By: Relevance
“…Adding age to the model significantly increased the adjusted R 2 values for the whole model for all conditions, indicating age is an important factor that is associated with WMH and dual task gait ( Table 3 ). The literature parallels this finding showing DTC increases and overall cognitive ability decreases, while WMH burden increases, with age ( Murman, 2015 ; Sartor et al, 2017 ; Garnier-Crussard et al, 2020 ). Future studies should examine age-related imaging changes, such as brain atrophy and structural and functional connectivity.…”
Section: Discussionsupporting
confidence: 53%
“…Adding age to the model significantly increased the adjusted R 2 values for the whole model for all conditions, indicating age is an important factor that is associated with WMH and dual task gait ( Table 3 ). The literature parallels this finding showing DTC increases and overall cognitive ability decreases, while WMH burden increases, with age ( Murman, 2015 ; Sartor et al, 2017 ; Garnier-Crussard et al, 2020 ). Future studies should examine age-related imaging changes, such as brain atrophy and structural and functional connectivity.…”
Section: Discussionsupporting
confidence: 53%
“…As an exploratory aim, recognizing that the brain regions utilized during complex gait tasks is certainly not limited to the frontal cortex, we extended our LMM analyses to explore other brain regions which may be related to the (non-spatially localized) frontal brain activations seen with fNIRS. The regions identified in these analyses ( Supplementary Table 1) are not surprising as potentially related to gait function: for example, cerebral white matter is a surrogate measure of brain atrophy, caudate has been shown to be related to gait performance (Macfarlane et al, 2015), and fusiform and pre-cuneus gyri have been shown to be related to gait and visuo-spatial orientation (Malouin et al, 2003;Sartor et al, 2017).…”
Section: Exploratory Analysesmentioning
confidence: 99%
“…Advanced age, schooling, and clinical profile are some of the factors explored in studies of cognitive impairment in patients with PD [8][9][10][11] . However, the association between these variables and cognition, comparing groups of Brazilian elderly and nonelderly persons with PD, has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%